2015
DOI: 10.1016/j.livsci.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Allele substitution effects of IGF1, GH and PIT1 markers on estimated breeding values for weight and reproduction traits in Canchim beef cattle

Abstract: a b s t r a c tThe aim of this study was to evaluate the allele substitution effects of IGF1, GH and PIT1 markers on the estimated breeding values (EBVs) for birth (BW) and weaning weights (WW), weight at 12 (W12) and 18 (W18) months of age, weight (WFC) and age (AFC) at first calving, and scrotal circumference measured at 12 (SC12) and 18 (SC18) months of age in Canchim beef cattle. Maternal effects were considered for birth (BW maternal ) and weaning (WW maternal ) weight. Regression analyses were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…According to Daniela do Amaral Grossi et al (2015), the bIGF-1-SnaBI A allele was found to be associated with higher live weight at birth, weaning, 12 and 18 months of age in Canchim beef cattle. A.…”
Section: Discussionmentioning
confidence: 99%
“…According to Daniela do Amaral Grossi et al (2015), the bIGF-1-SnaBI A allele was found to be associated with higher live weight at birth, weaning, 12 and 18 months of age in Canchim beef cattle. A.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that the polymorphisms of GH/AluI, GH/MboII, PIT1/HindfI and IGF1/MspI genes reported in Indonesian native cattle were also observed in the population of Pesisir cattle. The insulin-like growth factor type 1 (IGF1), growth hormone (GH) and pituitary transcription factor (PIT1) are candidate genes for growth and reproduction traits because they participate on the hormonal system with a fundamental role in regulating animal's development (Grossi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PIT1 gene has been extensively studied in cattle, including Limousine Cattle (Dybus et al 2003), Iranian cattle (Javanmard et al 2005), Brahman cattle (Beauchemin et al 2006), Zebu (Curi et al 2006;Mukesh et al 2008), Canchim Cattle (Carrijo et al 2008;Grossi et al 2015), Podolica cattle , Southern Anatolian red cattle (Oztabak et al 2008 The objectives of the present study were to study (i) the polymorphism of the GH/AluI, GH/MBoII IGF1R/MspI, and PIT/Hinf1, (ii) to determine the frequency of alleles and genotypes for these polymorphisms, and (iii) to estimate the associations between these polymorphisms and average daily gain and body measurement in Pesisir cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The joint effect of genotype combinations was estimated by the deviation between the average OPV of the hybrids sharing the same genotype combination and the overall mean phenotype of the training population. Additionally, since some genotypes were observed in relatively low frequencies, to eliminate bias in marker genotype effect estimates, the allele frequency and allele substitution effect (ASE) of each marker were estimated and subsequently the breeding value was calculated based on the ASE value and the allele frequency (Ashraf, Jensen, Asp, & Janss, 2014; Grossi et al., 2015). When any genotype was not observed, the regression analysis was performed using only two pairs of data (Grossi et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, since some genotypes were observed in relatively low frequencies, to eliminate bias in marker genotype effect estimates, the allele frequency and allele substitution effect (ASE) of each marker were estimated and subsequently the breeding value was calculated based on the ASE value and the allele frequency (Ashraf, Jensen, Asp, & Janss, 2014; Grossi et al., 2015). When any genotype was not observed, the regression analysis was performed using only two pairs of data (Grossi et al., 2015). The GAP model was re‐adopted by using breeding values or the joint effect of genotype combination of all the markers, and the accuracy was determined by five‐fold and “leave‐one‐family‐out” cross‐validation.…”
Section: Methodsmentioning
confidence: 99%